Ghosting - Poyer, David (St. Martin's Press, 2010)
Dr. Jack Scales, a prominent neurosurgeon, is at the peak of his career. To celebrate, he decides to make up for lost time and buys a sailing yacht christened Slow Dance, for a family cruise to Bermuda. But the family is strained: Jack's wife Arlen is secretly considering leaving the marriage; Rick, their bipolar twenty year old son, may need to be committed to a group home; Haley, a rebellious teenager, would rather be anywhere but trapped on a boat with her family; and Jack himself is not prepared for the challenge of the open sea. Day by day, the Scales face mounting dangers. A lightning storm nearly destroys the boat, Ric's unstable condition worsens, and both Arlen and Haley realize that Jack is in over his head. Still, emerging from the storm, they find a fragile unity.until a man adrift on a raft leads them into danger against a terrifying gang of smugglers who will stop at nothing to gain control of Slow Dance.